Drosophila let-7 microRNA is required for remodeling of the neuromusculature during metamorphosis. - Sokol, N.S.; Xu, P.; Jan, Y.N.; Ambros, V. (Genes & Development, 2008)
The Drosophila let-7-Complex (let-7-C) is a polycistronic locus encoding three ancient microRNAs: let-7, miR-100, and fly lin-4 (miR-125). We find that the let-7-C locus is principally expressed in the pupal and adult neuromusculature. let-7-C knockout flies appear normal externally but display defects in adult behaviors (e.g., flight, motility, and fertility) as well as clear juvenile features in their neuromusculature. We find that the function of let-7-C to ensure the appropriate remodeling of the abdominal neuromusculature during the larval-to-adult transition is carried out predominantly by let-7 alone. This heterochronic role of let-7 is likely just one of the ways in which let-7-C promotes adult behavior.